Dilemmas concerning heart procurement in controlled donation after circulatory death - Kaffka genaamd Dengler, S. E.; Vervoorn, M. T.; Brouwer, M.; de Jonge, J.; van der Kaaij, N. P. (Frontiers in Cardiovascular Medicine, 2023)
With an expanding population at risk for heart failure and the resulting increase in patients admitted to the waiting list for heart transplantation, the demand of viable organs exceeds the supply of suitable donor hearts. Use of hearts after circulatory death has reduced this deficit. Two primary techniques for heart procurement in circulatory death donors have been described: direct procurement and perfusion and thoraco-abdominal normothermic regional perfusion. While the former has been accepted as an option for heart procurement in circulatory death donors, the latter technique has raised some ethical questions in relation to the dead donor rule. In this paper we discuss the current dilemmas regarding these heart procurement protocols in circulatory death donors.